How Much War Will We See? Estimating the Incidence of Civil War in 161 Countries - Elbadawi, Ibrahim; Sambanis, Nicholas (World Bank, Washington, DC, 2014)
Quantitative studies of civil war have focused either on war's onset, or its termination, producing important insights into these end points of the process. The authors complement these studies by studying how much war we are likely to observe in any given period. To answer this question, they combine recent advances in the theory of civil war initiation, and duration, and, develop the concept of war incidence, denoting th probability of observing an event of civil war in any given period. They test theories of war initiation, and duration against this new concept, using a five-year panel data set for 161 countries. Their analysis of the incidence of war corroborates most of the results of earlier studies, enriching those results by highlighting the significance of socio-ppolitical variables as determinants of the risk of civil war. Their findings: 1) Steps toward advancing political liberalization, or economic development reduce the risk of civil war, whatever the degree of ethno-linguistic fractionalization in a society. 2) This effect is amplified in polarized societies. The probability of civil war is lower in very homogeneous societies, and (less so) in more diverse societies. 3) In polarized societies, the risk of civil war can be reduced by political, rather than economic liberalization. At high levels of political freedom, ethnic diversity - even polarization - has a minimal impact on the risk of civil war. 4) Economic diversification that would reduce a country's reliance on primary exports would also reduce the risk of civil wars, especially in polarized societies. 5) In strategies for preventing civil war, political liberalization should be a higher priority than economic development, but the best possible results would combine political reform, economic diversification, and poverty reduction.